1987
DOI: 10.1148/radiology.162.1.3786770
|View full text |Cite
|
Sign up to set email alerts
|

Focal fat deposition in axial bone marrow: MR characteristics.

Abstract: One hundred fifty-eight magnetic resonance (MR) imaging studies of the spine were reviewed to assess the frequency and distribution of focal deposits with signal behavior typical of fat in the axial bone marrow. In addition, three fresh cadaveric spines were evaluated with MR imaging and subsequently sectioned for anatomic and histologic correlation. Macroscopic evaluation of the sectioned cadaveric specimens revealed well-defined, yellow areas within the bone marrow that correlated precisely with localized zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 0 publications
1
23
0
4
Order By: Relevance
“…Radiologic features of the bone marrow of the patients showed more heterogeneous and patchy distribution of the signal intensity compared to that of the referents. This is compatible with a report that regeneration of the hematopoietic cells in bone marrow expands from islands of regenerative centers 18,19) . Distribution of the signal indices among the referents showed a characteristic pattern simulating the curvature of thoracolumbosacral spine, i.e., high at lower thoracic spine, lowering as it comes along the lumbar spine, lowest at L4, then gets higher up to sacrum, highest at S1.…”
Section: Discussionsupporting
confidence: 93%
“…Radiologic features of the bone marrow of the patients showed more heterogeneous and patchy distribution of the signal intensity compared to that of the referents. This is compatible with a report that regeneration of the hematopoietic cells in bone marrow expands from islands of regenerative centers 18,19) . Distribution of the signal indices among the referents showed a characteristic pattern simulating the curvature of thoracolumbosacral spine, i.e., high at lower thoracic spine, lowering as it comes along the lumbar spine, lowest at L4, then gets higher up to sacrum, highest at S1.…”
Section: Discussionsupporting
confidence: 93%
“…Marrow changes occurring in L5 pedicles have been reported. Hajek et al [8] and de Roos et al [3] first noted MR signal changes of vertebral body end plates in response to degenerative disc disease. Modic et al [14,15] concluded that pathological changes such as the extent of vertebral body sclerosis correlate well with MR signal intensity changes in vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, skeletal marrow consists entirely of hematopoietic tissue [2,7,9,11]. However, a progressive conversion to fatty (yellow) marrow occurs with age, beginning in the peripheral skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…However, a progressive conversion to fatty (yellow) marrow occurs with age, beginning in the peripheral skeleton. This dynamic process is affected by biological aging, sex, and the amount of stress placed upon an individual bone [2,5,7]. A normal adult distribution is present after the age of 25 years, the red marrow being retained in the membranous bones, ribs, sternum and proximal long bones [9,11].…”
Section: Discussionmentioning
confidence: 99%